Long-wavelength (λ ≈ 16 µm), room-temperature, single-frequency quantum-cascade lasers based on a bound-to-continuum transition - Rochat, Michel; Hofstetter, Daniel; Beck, Mattias; Faist, Jérôme (My University, 2001)
Room-temperature operation of long-wavelength, Fabry–Perot and single-mode quantum-cascade lasers at λ ≈ 16 µm is reported. Multimode emission with pulsed peak power up to 400 mW at –40 °C and 220 mW at 30 °C is demonstrated. Single-mode emission up to 60 mW peak power has been achieved at 30 °C.